Case Study: The Surgical Management of Angiokeratoma Resulting from Radiotherapy for Penile Cancer. (2009) - Rees, Rowland; Freeman, Alex; Malone, Peter; Garaffa, Giulio; Muneer, Asif; Minhas, Suks
Abstract : Angiokeratoma is a rare, benign skin lesion and a recognised complication of radiation therapy. Here we describe a case of extensive angiokeratoma of the groin and external genitalia resulting from external beam radiation to that area in a patient with penile carcinoma. Furthermore, we outline the management of this problem by surgical reconstruction.